2020
DOI: 10.1002/pmrj.12379
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Functional Outcomes between Patients Admitted to Inpatient Rehabilitation after Initial Diagnosis Versus Recurrence of Glioblastoma Multiforme

Abstract: Background: Prior studies of inpatient rehabilitation of patients with brain tumor demonstrate similar functional gains as compared to other rehabilitation populations. There are few studies specifically examining the rehabilitation of patients with glioblastoma. Objective: To compare functional outcomes between matched patients admitted to acute inpatient rehabilitation after initial diagnosis of glioblastoma (iGBM) and after diagnosis of recurrent glioblastoma (rGBM). Design: A retrospective, case-matched st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Contrary to our hypothesis, our data suggest that GBM patients who have undergone a second resection progress as well as their single resection peers with regard to functional recovery following an IRU course. This is in line with Reilly et al's findings of similar functional outcomes in initial versus recurrent GBM, though, of note, only 60% of their recurrence group had resection before IRU admission 40 . Additionally, we found the gains in those with multiple resections may be achieved over a shorter IRU stay with an equivalent likelihood of being discharged home when compared to those with first resection.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Contrary to our hypothesis, our data suggest that GBM patients who have undergone a second resection progress as well as their single resection peers with regard to functional recovery following an IRU course. This is in line with Reilly et al's findings of similar functional outcomes in initial versus recurrent GBM, though, of note, only 60% of their recurrence group had resection before IRU admission 40 . Additionally, we found the gains in those with multiple resections may be achieved over a shorter IRU stay with an equivalent likelihood of being discharged home when compared to those with first resection.…”
Section: Discussionsupporting
confidence: 92%
“…Broadly, on our unit, we encountered two distinct groups of patients with regards to postoperative steroid administration: one group that was able to complete the regimen prior to discharge and a second group that was discharged still receiving steroids. Reilly et al did note in their study that steroid weaning was more successful in those with initial diagnosis of GBM than those with recurrence 40 . It is feasible that as the steroids are tapered, differences in functional recovery would become apparent between the two groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reilly et al compared functional outcomes of 25 patients with initial diagnosis glioblastoma multiforme with 25 demographic-and lesion-matched recurrent glioblastoma multiforme patients and found that there was no statistical difference in functional gains at discharge between the two groups [54]. The full table can be seen in Table 2.…”
Section: Inpatient Rehabilitationmentioning
confidence: 99%
“…Reilly et al 2020 [54] Retrospective case matched study comparing 25 patients with an initial diagnosis of glioblastoma multiforme with 25 demographic-and lesion-matched patients who had a diagnosis of recurrent glioblastoma multiforme.…”
Section: Inpatient Rehabilitationmentioning
confidence: 99%